Strategi Coping stress pada Mahasiswa yang Mengikuti Organisasi di Fakultas Psikologi Universitas Negeri Malang - Virgianto, Firsthiansyah Ardan; Pranida, Jawahiril; Liana, Mia Ade; Atmaja, Muhammad Zidansyah Dwi; Avezahra, Mutia Husna (Universitas Negeri Malang, 2022)
Abstract : Students of the Faculty of Psychology, State University of Malang in semester 5 have quite heavy academic demands when compared to the previous semester and coupled with the demands of assignments from the organizational activities they participate in. There is an academic load as well as many programs and responsibilities in the organization that must be completed, so the stress level can be higher. This type of research is descriptive qualitative research using a phenomenological approach. The subjects were three psychology students who were active in organizations. Methods of data collection through interviews and observation. This study aims to gather information and find out how strategies for coping with stress on students who participate in organizations at the Faculty of Psychology, State University of Malang. The results of the study found that there were three phases that participants went through when faced with conditions that caused a sense of stress, besides that, planful problem solving, and accepting responsibility type coping strategies were the strategies most used by students who joined organizations in the psychology faculty, State University of Malang. Abstrak: Mahasiswa Fakultas Psikologi Universitas Negeri Malang pada semester 5 memiliki tuntutan akademik yang cukup berat jika dibandingkan semester sebelumnya dan ditambah dengan tuntutan tugas dari kegiatan organisasi yang mereka ikuti. Adanya beban akademik dan juga banyaknya program dan tanggung jawab di organisasi yang harus diselesaikan, maka tingkat stres bisa menjadi lebih tinggi. Jenis penelitian ini adalah penelitian kualitatif deskriptif dengan menggunakan pendekatan fenomenologi. Subjeknya adalah tiga mahasiswa psikologi yang aktif berorganisasi. Metode pengumpulan data melalui wawancara dan observasi. Penelitian ini bertujuan untuk menggali informasi dan mengetahui bagaimana strategi coping stress pada mahasiswa yang mengikuti organisasi di fakultas psikologi Universitas Negeri Malang. Hasil penelitian menunjukkan bahwa terdapat tiga fase yang dilalui oleh partisipan ketika dihadapkan pada kondisi yang menimbulkan rasa stres, selain itu strategi coping jenis planful problem solving, dan accepting responsibility adalah strategi yang paling banyak digunakan oleh mahasiswa yang mengikuti organisasi di fakultas psikologi Universitas Negeri Malang.